US and CT of 2 pediatric cases of self-inflicted pneumoparotid and cervicofacial emphysema - François Chalard, MD; Méryle Laurent, MD; Eugénie Barras, MD; Seema Toso, MD (Radiology Case Reports)
Pneumoparotid is a rare cause of parotid swelling characterized by the presence of air in the Stensen's duct and/or the parotid gland. In children, it is often self-inflicted, due to psychiatric disorder or recreational habits (puffing the cheeks, blowing balloons, bruxism…). The diagnosis may be suggested by specific signs such as crepitus or foamy saliva flowing from the Stensen's duct. Here, we present 2 cases of involuntary self-inflicted pneumoparotid, diagnosed by ultrasound and CT, in a child and a teenager. Imaging is useful for diagnosis and excluding complications. Ultrasonography may be sufficient to make the diagnosis of pneumoparotid but is less sensitive than CT. CT can make the diagnosis, but also more completely explores the deep cervical spaces and the thorax, especially important in cases with respiratory symptoms. Treatment is usually conservative, in association with behavioral counselling or psychologic/psychiatric therapy, to avoid activities leading to intra oral pressure increase.